2021
DOI: 10.3389/fcell.2021.658820
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-Site Mutations in Transcription Factor Suppressor of Hairless Impact Notch Signaling Activity During Hematopoiesis in Drosophila

Abstract: The highly conserved Notch signaling pathway controls a multitude of developmental processes including hematopoiesis. Here, we provide evidence for a novel mechanism of tissue-specific Notch regulation involving phosphorylation of CSL transcription factors within the DNA-binding domain. Earlier we found that a phospho-mimetic mutation of the Drosophila CSL ortholog Suppressor of Hairless [Su(H)] at Ser269 impedes DNA-binding. By genome-engineering, we now introduced phospho-specific Su(H) mutants at the endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 98 publications
1
37
0
Order By: Relevance
“…core Notch response, N-only, NS-only). Indeed, recent reports point towards different post-translational modifications for Su(H) (Frankenreiter et al, 2021). However, whether they lead to different transcriptional programs, and whether they occur in vivo in the N and NS models, remain to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…core Notch response, N-only, NS-only). Indeed, recent reports point towards different post-translational modifications for Su(H) (Frankenreiter et al, 2021). However, whether they lead to different transcriptional programs, and whether they occur in vivo in the N and NS models, remain to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, an analogous cellular mechanism that compromises Su(H) DNA binding has previously been identified in Drosophila 33,34 . In this case, phosphorylation of Su(H) residue S269, which interacts with DNA, blocks DNA binding, and plays a role in fly hematopoiesis.…”
Section: Discussionmentioning
confidence: 86%
“…Having shown the RBPJL-SHARP interaction, we wanted to characterize the functional consequences and determine the repressive capacity of RBPJL at endogenous Notch target genes. As we previously found that the deletion of RBPJ results in the derepression of Notch target genes in a mature T cell line [ 19 ] and in HeLa cells [ 48 ], we now performed rescue experiments re-expressing RBPJ or RBPJL fused to GFP using RBPJ-depleted HeLa cells ( Figure 7 A,B).…”
Section: Resultsmentioning
confidence: 99%